Economic Aspects of Human Cloning and Reprogenetics - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2002)
This paper analyses the economic issues associated with human cloning and new reproductive technologies. We analyze the incentives for human cloning and its implications for the long run distribution of skills and income. We analyse models of human cloning for different motives, focusing on those which tend to produce new human beings with improved ability. We thus ignore purely therapeutic applications, which may well be the most likely ones to happen in the near future, but have no first-order implications for the long-run distribution of skills and income. An important consequence of these models is that if ability is genetically heritable, cloning tends to increase the proportion of high ability people in society, and that under some hypothesis the distribution of ability converges to a mass point at the highest possible ability level. Under weaker assumptions, it is shown that ability-reducing genes are eventually eliminated. However, if fertility is negatively correlated with ability, cloning leads to a strongly segregated society with a top-ability caste and a bottom ability one which produces clones of the top ability one. The paper also discusses the plausibility of these results in light on the evidence from economics and other sciences on marriage markets, child selection, assisted reproduction, and animals.
Keywords: J3; J2; J1; 330; human cloning; income distribution; ability; human capital; Gentechnik; Ökonomischer Anreiz; Humankapital; Theorie